Endovascular stenting for treatment of superior vena cava syndrome - K., Subramanyam; Kamath, Janardhan; Johny, Dilip; Joyes, Paul T. (Journal of Health and Allied Sciences NU, 2015)
Superior vena cava syndrome (SVCS) is a well-known manifestation of benign and malignant tumors of the upper mediastinum. Superior vena cava (SVC) obstruction and thrombosis caused by indwelling venous catheters is a growing problem in patients on regular haemodialysis. We present a 62-year-old woman with typical signs and symptoms of SVCS, secondary to thrombosis surrounding the indwelling central catheter who was treated with endovascular stenting by the percutaneous approach. We obtained both procedural success with complete restoration of blood flow and immediate relief of symptoms.
Keywords: SVCS; Endovascular stenting; thrombosis; central line